Strengthening Business Management of BUMDes Kertaraharja in Cibubuan Village, Conggeang District, Sumedang Regency - Noor, Laili Savitri; Hermawati, Ati; Imron, Sarojini; Firmansyah, Riza (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
The research results found that the institutional capacity of BUMDes in Cibubuan Village, Conggeang District, Sumedang Regency was generally not implemented optimally. This can be seen from several problems, namely limited active resources in BUMDes, the low quality of human resources, lack of BUMDes leadership, lack of information on BUMDes business development and socialization related to BUMDes businesses, the work flow is still not running according to the organizational structure, lack of training and the absence of well-made activity reports. The research method used is a qualitative approach. The primary data sources in this research were 6 people. The data collection techniques used include observation, interviews and documentation studies. To overcome the problem, efforts were made, including optimizing the economic potential of Cibubuan Village as a BUMDes business potential, conducting BUMDes Reorganization Socialization, conducting FGDs and discussions, business feasibility training, training that encourages the formation of village tourism businesses, social media training, Opak product branding training and then socializing it. to the community as well as training in making reports on business results carried out by each BUMDes business unit, holding scheduled meetings and discussions with the BUMDes director and administrators accompanied by the Village Headman.